2007
DOI: 10.1080/10871200701323066
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Angler Attitudes Toward Catch-Related Aspects of Fishing

Abstract: Although activity-general motivations in the context of recreational fishing have received attention previously, the catch-related aspects of recreational fishing are less well understood. Labeled as consumptive orientation, this article seeks to fill a gap in the literature concerning the measurement of these aspects. Based on a modified version of a scale originally developed by Graefe (1980), the authors performed a confirmatory factor analysis on scale responses from a sample of Texas anglers. The model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
(37 reference statements)
3
58
0
Order By: Relevance
“…Respondent's catch-related attitudes were measured using a 12-item scale that measures angler's attitudes toward four constructs of the catch experience: catching something, catching numbers of fish, catching big fish, and retaining their catch (Table 4) (Anderson, Ditton, & Hunt, 2007). Scale items were presented as statements of preference, and respondents were asked to rate their level of agreement with each statement on a 5-point scale (i.e., 1 = strongly disagree to 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Respondent's catch-related attitudes were measured using a 12-item scale that measures angler's attitudes toward four constructs of the catch experience: catching something, catching numbers of fish, catching big fish, and retaining their catch (Table 4) (Anderson, Ditton, & Hunt, 2007). Scale items were presented as statements of preference, and respondents were asked to rate their level of agreement with each statement on a 5-point scale (i.e., 1 = strongly disagree to 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Angler catch orientation includes attitudes about catching fish, the size and number of fish caught, and keeping or releasing fish (Anderson, Ditton, & Hunt, 2007). Research has generally found support for a four-factor structure of catch orientation: catching something, catching many fish, catching large/trophy fish, and keeping or releasing fish (Anderson et al, 2007;Carlin, Schroeder, & Fulton, 2012;Kyle, Norman, Jodice, Graefe, & Marsinko, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Weithman and Anderson (1978) developed the minimum length for the qualitylength category from the relationship between world-record length and fish quality, and related the minimum to a length that is 36-41% of the species-specific world-record length. Even though fish harvest is an important part of the fishing experience for most anglers (Matlock et al, 1988;Peyton and Gigliotti, 1989;Spencer, 1989), the actualized minimum length of a quality-length fish likely differs between catch-and-release-orientated anglers and harvestorientated anglers (Wilde and Ditton, 1994;Arlinghaus, 2006b;Anderson et al, 2007) The decision to harvest any given fish depends on the dynamic relationship of an anglers' expectation, or perceptions, of what can be potentially caught in the waterbody within the confines of the harvest regulation (Cook et al, 2001;Hunt et al, 2002;Anderson et al, 2007). In our study, we were unable to conclude that the restriction of the harvest regulation altered the self-imposed length limits across the species assessed.…”
Section: Species 2010 2011mentioning
confidence: 99%